BIOACTIVITY OF ENDOPHYTIC FUNGI EXTRACT ISOLATED FROM THE LEAVES OF MISTLETOE (Dendrophthoe pentandra (L.) Miq.) ON THE LIME PLANT (Citrus aurantifolia) - Hiras Habisukan, Ummi; Oktiansyah, Rian; Noviyanto; Anjeli, Riri (Berita Biologi, 2024)
Mistletoe (Dendrophthoe pentandra (L.) Miq.) is a parasitic plant used in traditional medicine. This study evaluates the bioactivity of endophytic fungi in mistletoe . Endophytic fungal species were determined through morphological identification. Potato Dextrose Broth (PDB) media was used for the cultivation, and ethyl acetate was used as solvent to extract secondary metabolites. The antioxidant test was carried out using the DPPH method, while the paper disc diffusion method performed the antibacterial test. A total of 4 isolates of endophytic fungi were obtained from mistletoe leaves, namely isolates DB1 – DB4. The results of morphological analysis showed that DB1 was Paecilomyces sp., DB2 was Papulaspora sp., DB3 was Aspergillus sp., and DB4 was Mucor sp. The endophytic fungus DB3 (Aspergillus sp.) showed the most potential antioxidant and antibacterial activity. This endophytic fungal extract can potentially be a source of new drugs through further research by isolating the active compound.